Lembaga Bipartit Sebagai Mekanisme Pencegahan Konflik Industrial di Indonesia - Kelana, Dewa Sukma; Mudawaroh (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Industrial conflicts remain a challenge in labor relations in Indonesia and require effective preventive mechanisms. Bipartite institutions are designed as forums for communication between employers and workers to prevent industrial disputes at the company level; however, their effectiveness in practice remains questionable. This study aims to analyze the role and effectiveness of Bipartite Institutions as a mechanism for preventing industrial conflicts and to identify the factors that influence their performance. The study employs a legal-empirical approach using qualitative methods. Data were collected through in-depth interviews with Bipartite Institution officials, company management, labor union representatives, and officials from the Department of Labor, supplemented by an analysis of relevant regulations and documents. The data analysis technique used is descriptive-analytical qualitative data analysis. The research findings indicate that the Bipartite Institution has not yet functioned optimally as an instrument for preventing industrial conflicts. Major constraints include weak management commitment, low capacity of the board members, minimal government oversight, and an imbalance in the relationship of interests that renders bipartite dialogue merely a formality. However, companies that consistently activate the Bipartite Institution tend to have lower levels of disputes. This study underscores the importance of strengthening the institutional framework and capacity of Bipartite Institutions to foster more harmonious and equitable industrial relations